Pembelajaran digital geografi melalui articulate storyline pada materi mitigasi bencana longsor - Safitri, Wilis Sukma; Soekamto, Hadi; Irawan, Listyo Yudha; Sumarmi, Sumarmi; Pertiwi, Ella (Universitas Negeri Malang, 2023)
This development research aims to produce a digital learning media product based on an articulate storyline of landslide disaster mitigation material. Development is carried out using the ADDIE model, which focuses on the ADD (Analysis, Design, and Development) stage. The results of the learning media validation obtained a feasibility value of 87 percent in terms of material, 93 percent in terms of learning media, and 75 percent in terms of language. Overall the average value obtained is 85 percent which is included in the very decent classification. In addition, the results of learning media trials conducted on students in terms of appearance, material, and language showed an average value of 97 percent which was classified as very feasible. Not only that, the superior components of learning media in the form of student activities in the form of independent exploration and earth studios, pop-up menus, and a combination of video and audio also get very decent ratings. This makes articulate storyline-based digital learning media suitable for use and implementation in learning activities. Penelitian pengembangan ini bertujuan untuk menghasilkan suatu produk media pembelajaran digital berbasis articulate storyline pada materi mitigasi bencana longsor. Pengembangan yang dilakukan menggunakan model ADDIE yang difokuskan pada tahap ADD (Analysis, Design, and Development). Hasil validasi media pembelajaran mendapatkan nilai kelayakan sebesar 87 persen dari segi materi, 93 persen dari segi media pembelajaran dan 75 persen dari segi bahasa. Secara keseluruhan rata-rata nilai yang diperoleh sebesar 85 persen yang masuk pada klasifikasi sangat layak. Selain itu, hasil uji coba media pembelajaran yang dilakukan kepada siswa dari segi tampilan, materi dan bahasa menunjukkan diperoleh nilai rata-rata sebesar 97 persen yang masuk klasifikasi sangat layak. Tidak hanya itu, komponen unggulan pada media pembelajaran berupa kegiatan siswa berupa eksplorasi mandiri dan earth studio, pop-up menu serta kombinasi video dan audio juga mendapatkan penilaian sangat layak. Hal tersebut menjadikan media pembelajaran digital berbasis articulate storyline telah layak digunakan dan diimplementasikan dalam kegiatan pembelajaran.